The Influence of Entrepreneurial Orientation and Market Orientation on the Performance of SMEs in West Sumatra with Social Media Moderation - Sri Ramadhan; Rangga Wisanggara; Alfi Syukri Rama; Rama Wahyudin; Atifah Asha Kamila (Jurnal Ecogen, 2026)
This study aims to examine the influence of entrepreneurial orientation and market orientation on the performance of Small and Medium Enterprises (SMEs) in West Sumatra during the transition period of the Covid-19 pandemic, as well as to analyze the moderating role of social media usage. This research employs a quantitative approach using survey data collected from 115 SME owners across four cities in West Sumatra. The data were analyzed using Structural Equation Modeling with Partial Least Square (SEM-PLS). The results indicate that entrepreneurial orientation has a positive and significant effect on SME performance, suggesting that innovativeness, proactiveness, and risk-taking behavior play a crucial role in improving business outcomes. Market orientation also shows a positive and significant influence on SME performance, highlighting the importance of customer focus, competitor awareness, and market intelligence in enhancing business performance. Furthermore, social media usage has a direct positive effect on SME performance; however, it does not significantly moderate the relationship between entrepreneurial orientation and SME performance, nor between market orientation and SME performance. These findings imply that although social media has the potential to support business activities, its utilization by SMEs in West Sumatra has not been strategically optimized to strengthen entrepreneurial and market orientations. Overall, SME performance during the post-pandemic transition period is predominantly driven by internal strategic orientations rather than the moderating role of social media.